The Impact Of The Components Of Population Growth On The Gross Domestic Product In Syria - Akroush, Mohmad; Hmedi, Ali (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of this study was to determine extent of the significant effect of each component of population growth(total fertility rate, crude mortality rate, migration net) on the gross domestic product in Syria. The research also aims at finding out if there is a significant mathematical model linking between all components of population growth and gross domestic product in Syria. The most important results were: - There is a statistically significant effect of the fertility rate on gross domestic product in Syria. - There is no statistically significant effect of the mortality rate on gross domestic product in Syria. - There is a statistically significant effect of migration net on gross domestic product in Syria. - There is a significant mathematical model linking between all components of population growth and gross domestic product in Syria. هدفت هذه الدراسة إلى معرفة أثر مكونات النمو السكاني المتمثلة بـ ( معدل الخصوبة الكلية، معدل الوفيات الخام، صافي الهجرة) على الناتج المحلي الإجمالي في سورية خلال الفترة 1990- 2017، كما يهدف البحث إلى معرفة فيما إذا كان هناك نموذج رياضي يربط بين جميع مكونات النمو السكاني والناتج المحلي الإجمالي في سورية. وكانت أهم النتائج: - يوجد أثر ذو دلالة إحصائية لمعدل الخصوبة الكلية على الناتج المحلي الإجمالي في سورية. - لا يوجد أثر ذو دلالة إحصائية لمعدل الوفيات الخام على الناتج المحلي الإجمالي في سورية. - يوجد أثر ذو دلالة إحصائية لصافي الهجرة على الناتج المحلي الإجمالي في سورية. - يوجد نموذج رياضي يربط بين جميع مكونات النمو السكاني والناتج المحلي الإجمالي في سورية.